Properties of bismaleimide resin modified with polyrotaxane as a stress relaxation material. Issue 8 (10th June 2018) - Ohtsuka, Keiko; Zhao, Changming
Abstract: In this study, 4, 4′‐diphenylmethane bismaleimide (BMI)/2, 2′‐diallylbisphenol A (DABPA) resin was modified with polyrotaxane (PR) as a stress relaxation material. Based on a dynamic mechanical analysis and various properties of the cured resin, the influence of the motion of PR on the cured properties of BMI/DABPA/PR alloy is discussed. The cyclic molecule α‐cyclodextrin (α‐CD) that is threaded onto the PR axis contains a methacryl group in its side chain that reacts with the allyl group of BMI/DABPA resin. The methacryl group of PR reacted with the allyl group of BMI/DABPA matrix resin to form a transparent and dense network structure, so that the glass transition temperature was increased with increasing PR concentration. In addition, the toughness, impact resistance and adhesiveness of BMI/DABPA resin were improved by modification with PR. These results indicate that the poly(ethylene glycol) chain, which is the axial polymer of the PR, moves in the space formed by the cavities of the threaded α‐CD and the surrounding BMI/DABPA resin matrix in the glassy state, thereby relaxing the internal stress applied to BMI/DABPA/PR resin. The range of applications of BMI/DABPA resin modified with PR may expand into fields requiring high heat resistance in addition to excellent toughness and adhesiveness. © 2018 Society of Chemical Industry Abstract : The fracture toughness value was up to 1.6 times and the impact strength was up to 4.1 times by modification with PR, compared with unmodified resin.